Indoor Air Quality (IAQ): Accuracy of Natural Ventilation for Temperature, Air Flow Rate and Relative Humidity (RH) in School Building Classrooms - Norazman, Norsafiah; Irfan Che Ani, Adi; Haslina Jaâ€™afar, Nor; Azry Khoiry, Muhamad (International Journal of Engineering and Technology, 2018)
Indoor Air Quality (IAQ) is an essential matter in achieving studentsâ€™ satisfaction for the learning process. Buildingâ€™s orientation is a factor that may encourage sufficient natural ventilation for the classroom occupants. Inadequate ventilation is an issue for most existing classrooms. The purpose of this paper is to analyze the accuracy of natural ventilation in classrooms. Therefore, experimental on 20 classrooms has been conducted by using Multipurpose Meter at secondary school buildings in Malaysia. The findings indicated that the accuracy of natural ventilation testing was below the permissible limits throughout the hours monitored, thus this may cause potential health hazards to the students. Temperature and air flow rates were lower than 23 Â°C and 0.15 m/s respectively, it fulfilled the basic requirements as a standard learning environment. However, measurements taken showed the overall relative humidity (RH) in the classrooms can be categorized as acceptable with 40% to 70% range. On the basis of these findings, it is evident that naturally ventilated classrooms are important especially due to energy efficiency, whereas mechanical ventilation should only be installed as an alternative under extremely hot weather conditions.Â Â Â